Variation of soil organic carbon stability in restored mountain marsh wetlands - Xin Yang; Jiao Zheng; Dan Yang (Scientific Reports, 2024)
Abstract The replacement of farmland by native hygro-plants is increasingly common globally within the context of wetland ecosystem restoration. Understanding the long-term effects of this replacement on the abundance and persistence of soil organic carbon (SOC) in mountain marshes is important for soil carbon management. Here, the restored plateau mountain marshes of Duliu River Wetland Provincial Nature Reserve, China was selected. The properties, soil moisture content (SMC), pH, texture, free-form iron oxides ( $$\:{\text{F}\text{e}}_{\text{d}}$$ ), amorphous iron oxides ( $$\:{\text{F}\text{e}}_{\text{o}}$$ ), mineral-associated organic carbon (MAOC), and iron-bound organic carbon (Fe-OC) were analyzed in topsoil samples (0 ~ 20 cm) during the restoration of rice paddies to Sphagnum palustre L. wetlands for 0, 2, 10, and 20 years. Natural Sphagnum wetlands were also used as the control. We found that marsh restoration increased SMC, $$\:{\text{F}\text{e}}_{\text{o}}$$ , $$\:{\text{F}\text{e}}_{\text{d}}$$ , $$\:{\text{F}\text{e}}_{\text{o}}$$ / $$\:{\text{F}\text{e}}_{\text{d}}$$ , SOC, MAOC, Fe-OC, Fe-OC/SOC, but decreased the MAOC/SOC ratio. MAOC/SOC ratio of marshes were expectedly lower than the proportion of labile SOC in total SOC during the restoration period. SMC, SOC, and MAOC were higher in the natural Sphagnum wetlands than in other habitats. Both SOC and Fe-OC/SOC were positively correlated with SMC, $$\:{\text{F}\text{e}}_{\text{o}}$$ , $$\:{\text{F}\text{e}}_{\text{d}}$$ , $$\:{\text{F}\text{e}}_{\text{o}}$$ / $$\:{\text{F}\text{e}}_{\text{d}}$$ , and Fe-OC, but negatively correlated with soil pH. MAOC/SOC was negatively correlated with SMC, $$\:{\text{F}\text{e}}_{\text{o}}$$ and $$\:{\text{F}\text{e}}_{\text{o}}$$ / $$\:{\text{F}\text{e}}_{\text{d}}$$ . These results emphasized the significance of reconverting rice paddies to marsh wetlands for increasing the sequestration of labile SOC and Fe-OC. Further studies are required to identify and quantify the organo-mineral stabilization mechanisms of SOC at the different SOC fractionations throughout the restoration period.